Dog Pulling on the Leash: Effects of Restraint by a Neck Collar vs. a Chest Harness - Shih, Hao-Yu; Phillips, Clive J. C.; Mills, Daniel S.; Yang, Yifei; Georgiou, Fillipe; Paterson, Mandy B. A. (Frontiers in Veterinary Science, 2021)
Leash pulling is a concern for dog owners and can be detrimental to the health and welfare of dogs. Neck-collars and back-connection harnesses are popular restraint types. Harnesses have been proposed as a better option considering canine health and welfare. Anecdotally, dogs pull more when wearing a back-connection harness; however, there is no scientific evidence for this perception. This study aimed to investigate how strongly dogs pull on the lead to achieve a food treat or toy under restraint by a neck-collar versus a back-connection harness. A within-subject counterbalanced design was used involving 52 shelter dogs. A customized canine leash tension meter was connected to the collar or harness to record the pulling of dogs, including measuring the maximal and mean leash tension and the time spent pulling. In addition, dog behaviours were recorded using two cameras from two directions. The maximal and mean leash tension and the pulling time were greater under restraint by harness when attracting dogs with food treats. No significant difference between harness and collar was found in potential stress-related behaviours (e.g. tail and ear positions, lip-licking and panting). However, dogs looked at the experimenter more often when restrained by harness than collar in the food treat attraction test. No significant difference was detected between harness and collar with respect to leash tension and stress-related behaviours in the toy attraction test. These findings suggest that dogs tend to pull stronger and more steadily when wearing a back-connection harness compared to a neck collar to reach the food treat but not the toy.